Risk Factors Associated with Overweight and Obesity among Women of Reproductive Age Residing in Dharan Sub-Metropolitan City, Nepal - Bhattarai, Prabina; Bhattarai, Richa; Khadka, Dambar Bahadur (Himalayan Journal of Science and Technology, 2018)
Overweight and obesity is an emerging public health issue in developed world and is also rapidly increasing in developing world. This study was carried out to determine the prevalence and associated risk factors of overweight and obesity among women of child bearing age. A cross sectional study was conducted among 206 women residing in Dharan Sub-Metropolitan city of eastern Nepal. BMI, waist circumference and waist to hip ratio were used as indicators for overweight and obesity based on WHO classification and IDF Classification criteria. Association between socioeconomic factors, dietary factors, physical activity, behavioral factors and health related factors with overweight and obesity among women were assessed by using chi square test. Results showed that 50.48% women were overweight and obese (BMI > 25), while 89% based on WHR and, 75.2% based on waist circumference were abdominally obese. The study also showed that age, marital status, size of family, parity, drinking habit and protein intake were major risk factors for overweight and obesity based on BMI. Abdominal obesity based on waist circumference measurement was associated with age, marital status, parity, TV watching while eating habit, contraceptives use, eating outside and protein intake. The high prevalence of overweight and obesity, and diverse natures of associated risk factors among child bearing age women in Dharan showed that more research in this aspect need to be carried out and concerned agencies should focus on identified risk factors for interventions to reduce existing problems of overweight and obesity among women of reproductive age.